Incident infection following acute kidney injury with recovery to baseline creatinine: A propensity score matched analysis - Griffin, Benjamin R.; You, Zhiying; Holmen, John; SooHoo, Megan; Gist, Katja M.; Colbert, James F.; Chonchol, Michel; Faubel, Sarah; Jovanovich, Anna (PloS one, 2019)
Severe acute kidney injury (AKI) is associated with subsequent infection. Whether AKI followed by a return to baseline creatinine is associated with incident infection is unknown. We hypothesized that risk of both short and long term infection would be higher among patients with AKI and return to baseline creatinine than in propensity score matched peers without AKI in the year following a non-infectious hospital admission. Retrospective, propensity score matched cohort study. We identified 494 patients who were hospitalized between January 1, 1999 and December 31, 2009 and had AKI followed by return to baseline creatinine. These were propensity score matched to controls without AKI. The predictor variable was AKI defined by International Classification of Diseases, Ninth Revision (ICD-9) codes and by the Kidney Disease Improving Global Outcomes definition, with return to baseline creatinine defined as a decrease in serum creatinine level to within 10% of the baseline value within 7 days of hospital discharge. The outcome variable was incident infection defined by ICD-9 code within 1 year of hospital discharge. AKI followed by return to baseline creatinine was associated with a 4.5-fold increased odds ratio for infection (odds ratio 4.53 [95% CI, 2.43-8.45]; p<0.0001) within 30 days following discharge. The association between AKI and subsequent infection remained significant at 31-60 days and 91 to 365 days but not during 61-90 days following discharge. Among patients from an integrated health care delivery system, non-infectious AKI followed by return to baseline creatinine was associated with an increased odds ratio for infection in the year following discharge.